2014 IEEE International Symposium on Circuits and Systems (ISCAS) 2014
DOI: 10.1109/iscas.2014.6865218
|View full text |Cite
|
Sign up to set email alerts
|

Reconfigurable Lab-on-Chip platform for algae cell manipulation

Abstract: In this paper, we present a new dielectrophoretic microfluidic technique in a modular Lab-on-Chip (LoC) platform. The proposed LoC has a reconfigurable topology. It generates a wide range of signals depending on the analyzed liquid with a variable frequency up to 1.2 MHz. In addition, a programmable phase shift circuit with a minimum phase step of 3.6 • for each signal is implemented. The amplitude of each signal can be adjusted independently, and the latter can be distributed through 64 bidirectional electrod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Song et al 213 also reported a constriction-based iDEP device for separation of C. vulgaris and P. subcapitata. Miled et al 214 reported a microelectrode array device for pDEP-and nDEPbased manipulation of algae cells. Graham et al 215 used a commercially available metal microelectrode for dielectrophoretic manipulation of E. viridis cells and intercellular organelles.…”
Section: ■ Technical Realization Platforms For Depmentioning
confidence: 99%
“…Song et al 213 also reported a constriction-based iDEP device for separation of C. vulgaris and P. subcapitata. Miled et al 214 reported a microelectrode array device for pDEP-and nDEPbased manipulation of algae cells. Graham et al 215 used a commercially available metal microelectrode for dielectrophoretic manipulation of E. viridis cells and intercellular organelles.…”
Section: ■ Technical Realization Platforms For Depmentioning
confidence: 99%
“…Furthermore, some LoC are fully integrated systems with electrodes covered by a membrane inside microfluidic micro-channels while other systems use electrodes fabricated on a simple printed circuit board (PCB) [9]- [11]. Obviously, it is practically impossible to have a test-bench setup versatile enough to cover all kinds of applications where LoC are used.…”
mentioning
confidence: 99%
“…In addition the same platform was used to detect algae concentration in water. Obtained results are published in [11].…”
mentioning
confidence: 99%